Growth and departure dynamics of isolated vapour bubbles: an improved CFD model for bubble evolution in pool boiling - Nadim, Nima; Chandratilleke, Tilak (2014)
An improved CFD model is developed and evaluated to be used as a mechanistic model for bubble inception, growth and departure mechanism by accounting for wide range of parameters and acting forces. Critical deficiencies of earlier CFD models are recognised, discussed and alternative schemes are suggested. Well-trusted bulk empirical models are used for a limited examination and validation of model whilst heating intensity varies and satisfactory agreement supported accurate qualitative post-processing of bubble evolution in pool boiling.